Great powers and Southeast Asian Regional security strategies : omni-enmeshment, balancing and hierarchical order - Goh, Evelyn (2009)
The small and medium-sized states in Southeast Asia have undergone significant geostrategic changes with the end of the Cold War and the rise of China. There has been a lively debate over the last decade about whether these countries would balance against or bandwagon with China, and how their relations with the other major powers in the region would change. Recent works that argue against the simple dichotomy of balancing versus bandwagoning are correct in asserting that Southeast Asian countries do not want to choose between the two major powers, the U.S. and China. But this paper goes futher to present the results of an empirical study that fleshes out the conceptual thinking that underlies this avoidance strategy. It finds that instead of merely adopting tactical or time-buying policies, key Southeast Asian states have actively tried to influence the shaping of the new regional order. It argues that key Southeast Asian states in fact have (a) distinct conceptualisations of two main pathways to order in the region - omni-enmeshment of major powers and complex balance of influence; and (b) a concrete vision of the preferred power of distribution outcome, which is a hierarchical regional order.